(3eLehY Hg cdGe GdCOHGA GdeJCNQhf hGdTYQGA GdeJbOejfs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO agPG eLehY ef cdGe GdeJCNQjf hGdTYQGA GdeJbOejf ChOYJg ef cd af CMSfg hHGddg GdeSJYGf s
(3BNQgG (B:s
(3hgPG BNQ eG ChQOfGg ef gPG GdeLehY hGdMeO ddg hMOgq s
(3Vef eLehY , JQJjHgG (B: 3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs